Analisis Efektivitas dan Waktu Pengurasan Kantong Lumpur Saluran Primer Daerah Irigasi Glapan Timur - Pramsetya, Alviola Parentika; Kuncoro, Ahmad Hakim Bintang; Abdurrahman, Abbas; Budiningrum, Diah Setyati (Jurnal Civil Engineering Study, 2023)
Irrigation is an effort to drain water from the source to agricultural land to meet the water needs of the land. Irrigated Area (I.A.) East Glapan needs help in the form of channels that carry too much mud or sediment material, thus hindering water distribution to the farthest lands. The lack of optimal mud bag building in the primary channel causes this. Based on these problems, it is necessary to check the effectiveness of the East Glapan I.A. mud bag. The analysis stage involves sediment sample tests and sediment transport calculations using the Shield, Einstein, and Mayer-Patter & Muller (MPM) methods, checking the deposition effectiveness and calculating the draining time. Based on the results of sediment transportation calculations, the highest value of 37.15 tons/day was obtained based on the MPM method. A settling efficiency value of 86.10% was obtained for the effectiveness of sludge bags. Then to optimize the performance of the mud bag, according to the calculation results, it is necessary to drain the mud bag of I.A. East Glapan every four months.